INOVASI PEMANFAATAN KAIN PERCA ULOS SEBAGAI PELESTARIAN BUDAYA BATAK DALAM MENGHADAPI BONUS DEMOGRAFI 2045 (STUDI KASUS KAMPUNG ULOS HUTARAJA, KABUPATEN SAMOSIR) - Irfan Aji Pratama (Bajang Institute, 2025)
This research examines innovation in the utilisation of Ulos patchwork as a strategy to preserve Batak culture in the context of the 2045 demographic bonus. The study was conducted in Hutaraja Ulos Village, Lumban Suhi-suhi Toruan Village, which is known as the centre of traditional ulos weaving. The phenomenon of the low interest of the younger generation in traditional products, the lack of regeneration of weavers, and the accumulation of patchwork waste are the main background of this research. The methods used include participatory observation, in-depth interviews, and designing product innovations based on Gen Z preferences. The results show that the younger generation is interested in products that are aesthetic, functional, and sustainable. Ulos patchwork, which was previously considered waste, was successfully transformed into modern souvenirs such as totebags, straps, and pouches that are relevant to Gen Z's lifestyle. This innovation not only contributes to cultural preservation, but also opens up new economic opportunities for local communities, as well as supporting circular economy and environmentally friendly practices. Therefore, this strategy is believed to be able to bridge traditional values with the demands of the times, while making Gen Z the driving force of cultural preservation in the era of demographic bonus